The cytologic and histologic diagnosis of ureteral fibroepithelial polyp in a dog. (17th December 2020) - Etzioni, Athema L.; Raskin, Rose E.; Van Alstine, William G.; Yu, Jeff
Abstract: A 6‐year‐old, intact male, brindled, 30‐Lb English Bulldog presented to the Purdue University Veterinary Teaching Hospital with a recurrent history of hematuria, periuria, and lethargy that responded temporarily to antibiotic therapy. The work‐up included a complete blood count, serum biochemical profile, complete urinalysis, diagnostic imaging (abdominal radiographs and ultrasound with contrast urography), and exploratory laparotomy. The diagnostic imaging findings and subsequent exploratory revealed a unilateral, intraluminal, right‐sided, 3‐cm ureteral mass extending from the proximal ureter into the renal pelvis. Subsequently, a unilateral right‐sided ureteronephrectomy followed by biopsy with cytopathology/cytology (impression smears) and histopathology of the ureteral mass was performed. The cytopathologic interpretation was benign mesenchymal proliferation with mildly atypical urothelial cells. The association of this mass with vascular tissue and a benign nuclear appearance on cytology is similar to reports of fibroepithelial polyps (FEPs) and myxomatous tumors. Histopathology diagnosed the mass as an FEP. Cytopathology proved useful in the presumptive diagnosis of this benign urothelial polyp. To the authors' knowledge, this is the first report using cytopathology to depict and characterize FEPs in veterinary and human medical literature.